2012
DOI: 10.23939/chcht06.03.327
|View full text |Cite
|
Sign up to set email alerts
|

Biodamages and Protection of Leather and Fur

Abstract: The paper presents the information about biodamages and protection of leather and fur. The contributors put a special emphasis on rawhide microflora, putrefied hide microflora, effect of prior operations on bioresistance of leather, interesting facts, fur skin structure and properties changes by microorganisms and the methods of leather preservation against microorganism impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…This also explains why the temperatures corresponding to the peaks in storage modulus for tanned hide were slightly higher than for pickled hide (Figure ). These results agree with those by Pekhtasheva et al ., where it was observed that elastic properties of collagen increases with tanning. The temperature corresponding to the second peak of storage moduli for tanned hide was greater than that for pickled hide.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…This also explains why the temperatures corresponding to the peaks in storage modulus for tanned hide were slightly higher than for pickled hide (Figure ). These results agree with those by Pekhtasheva et al ., where it was observed that elastic properties of collagen increases with tanning. The temperature corresponding to the second peak of storage moduli for tanned hide was greater than that for pickled hide.…”
Section: Resultssupporting
confidence: 93%
“…It improves the thermal stability by increasing the melting temperature, shrinkage temperature, or denaturation temperature . The results agree with those reported by Pekhtasheva et al . In both pickled and tanned hides, nonirradiated samples had the highest melting temperature compared to solar‐irradiated samples.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Not all bioplastics are biodegradable and decompose faster than synthetic polymers [16]. e main methods for preparing biodegradable polymers are as follows [17]:…”
Section: General Information On Biodegradable Polymersmentioning
confidence: 99%